Anode Based on Porous Silicon Films Using Polymer Electrolyte for Lithium-Ion Microbatteries. (7th August 2015) - Chaudoy, V.; Luais, Erwann; Ghamouss, F.; Defforge, Thomas; Desplobain, S.; Gautier, G.; Wolfman, J.; Houdbert, J.-C.; Tran-Van, François; Sakai, J.
Abstract : In this paper, the preparation of an all solid-state lithium-ion microbattery is presented with original core materials : a gel polymer electrolyte (GPE) and a macroporous silicon (pSi) as the anode. The preparation and the synthesis of GPE consist of solubilizing a linear polymer (PVdF-HFP : poly(vinylidene fluoride-co-hexafluoropropylene) with an ionic liquid (P13FSI : Pyrrolidinium bis(fluorosulfonyl)imide) and a lithium salt (LiTFSI : lithium bis-trifluoromethanesulfonimide). The polymer film is transparent, self-supported and presents an ionic conductivity of 1.88 mS.cm -2 at 25°C. GPE compatibility with a Li/LiCoO2 system, with a Li/pSi half-cell and finally with a pSi/LiCoO2 lithium-ion microbattery, is demonstrated through 30 galvanostatic cycles. The full cell reaches a discharge capacity of 173 µAh/cm 2 at 167 µA/cm 2 with a coulombic efficiency upper than 99 % after 7 cycles of charge and discharge.